Dry transfer of CVD graphene using MoS2‐based stamps. Issue 7 (14th June 2017) - Banszerus, Luca; Watanabe, Kenji; Taniguchi, Takashi; Beschoten, Bernd; Stampfer, Christoph
Abstract : Recently, a contamination‐free dry transfer method for graphene grown by chemical vapor deposition (CVD) has been reported that allows to directly pick‐up graphene from the copper growth substrate using a flake of hexagonal boron nitride (hBN), resulting in ultrahigh charge carrier mobility and low overall doping. Here, we report that not only hBN, but also flakes of molybdenum disulfide (MoS2 ) can be used to dry transfer graphene. This, on one hand, allows for the fabrication of complex van‐der‐Waals heterostructures using CVD graphene combined with different two‐dimensional materials and, on the other hand, can be a route toward a scalable dry transfer of CVD graphene. The resulting heterostructures are studied using low temperature transport measurements revealing a strong charge carrier density dependence of the carrier mobilities (up to values of 12, 000 cm 2 /(Vs)) and the residual charge carrier density fluctuations near the charge neutrality point when changing the carrier density in the MoS2 by applying a top gate voltage. Abstract : Graphene grown by chemical vapour deposition (CVD) is dry‐transferred from its growth substrate onto hexagonal boron nitride with the help of exfoliated MoS2 flakes, for the first time allowing the solution‐free fabrication of complex van‐der‐Waals heterostructures from CVD graphene. Transport measurements reveal that the disorder potential in the graphene and the maximum resistance at the Dirac point strongly depend on the doping of the MoS2 layer.